Perspectives of scholars on the nature of sustainability: a survey study. Issue 1 (24th October 2019) - Aminpour, Payam; Gray, Steven; Richardson, Robert; Singer, Alison; Castro-Diaz, Laura; Schaefer, Marie; Ramlan, Mohd Aswad; Chikowore, Noleen Rutendo
Abstract : Purpose: This paper aims to investigate different ways in which faculty members of sustainability-related departments in universities across the world perceive, understand and define sustainability and how these definitions are linked to their demographics and epistemological beliefs. Design/methodology/approach: Scholars from different disciplines investigate the sustainability of social-ecological systems from different perspectives. Such differences in the understanding of, and approaches to, sustainability have created ambiguity within the field and may weaken its effectiveness, impact and reputation as a field of research. To contribute to the discussion about sustainability definition, a survey was conducted involving university faculty members working in sustainability-related academic departments around the world. Participants' responses were analyzed using SPSS 24.0 involving descriptive and inferential statistics and principle component analysis. Additionally, responses to open-ended questions were qualitatively analyzed. Findings: Factor analysis on sustainability definition items reveal four emergent universal definitions of sustainability, labeled as Environmentalism concerns, Common understanding, neo-Malthusian environmentalism and Sustainability as well-being. Statistical analyses indicate that individuals from developed countries are more likely to define sustainability as Environmentalism and Common understanding; however, individuals from developing countries tend to define sustainability as well-being. Also, more heavily engaged scholars in interdisciplinary research of sustainability are more likely to perceive sustainability as Common understanding. Logistic Regression models demonstrate a connection between epistemological perspectives of researchers and sustainability definitions. Qualitative content analysis indicates that interdisciplinarity and collaboration are the most common challenges to sustainability research. Originality/value: The findings of this study demonstrate disconnects between scholars from developing and developed countries in understanding and defining sustainability, and these disconnects may present further challenges for global sustainability scholarship.